2020
DOI: 10.21203/rs.3.rs-21725/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small Particle Aerosol Exposure of African Green Monkeys to MERS-CoV as a Model for Highly Pathogenic Coronavirus Infection

Abstract: Emerging highly pathogenic coronaviruses (CoV) are a global public health threat due to the potential for person-to-person transmission and higher mortality rates than common seasonal respiratory pathogens. Middle East respiratory syndrome coronavirus (MERS-CoV) emerged in 2012, causing lethal respiratory disease in approximately 35% of human cases.Primate models of highly pathogenic coronavirus infection are needed to support development of therapeutics or vaccines, but few models exist that recapitulate seve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…In 12 African green monkeys exposed to different target doses of aerosolized MERS-CoV, a dose-dependent increase of respiratory disease signs was observed. 26 In our study, we firstly showed that tracheal intubation or extubation were associated an increased likelihood of symptomatic SARS-CoV-2 infection. One possible explanation could be that a relatively high initial virus exposure might lead a high viral load in respiratory tract, thereby overcoming the barriers of the immune responses and causing symptomatic infection or even unfavorable disease outcome.…”
Section: Discussionmentioning
confidence: 74%
“…In 12 African green monkeys exposed to different target doses of aerosolized MERS-CoV, a dose-dependent increase of respiratory disease signs was observed. 26 In our study, we firstly showed that tracheal intubation or extubation were associated an increased likelihood of symptomatic SARS-CoV-2 infection. One possible explanation could be that a relatively high initial virus exposure might lead a high viral load in respiratory tract, thereby overcoming the barriers of the immune responses and causing symptomatic infection or even unfavorable disease outcome.…”
Section: Discussionmentioning
confidence: 74%
“…We project that masks will lead to a lower exposure viral load among newly infected people, particularly if both the transmitter and exposed individual are successfully masked. Animal models of SARS-CoV-1 and MERS (27,28,34), as well as challenge studies with influenza H1N1 in humans (35), all demonstrate that lower exposure dose is associated with less severe disease, and human data from the Hong Kong SARS-CoV-1 outbreak in Hong Kong suggest a similar trend (36). While data for SARS-CoV-2 in humans is lacking, it is notable that age-adjusted hospitalization and death rates may be decreasing since more widespread utilization of masks.…”
Section: Discussionmentioning
confidence: 99%
“…Another theoretical benefit of masks is reduction in exposure viral load which in animal models of SARS-CoV-1 and MERS, leads to less severe infection (26)(27)(28). Simulating under the assumption that 75% of people wear masks 75% of the time (i.e., a situation representing current levels of masking in the United States), we identified that viral load of a transmitter required to generate secondary infections increases slightly with higher implementation of more efficacious masks, particularly with dual masking of transmitters and exposed contacts (Fig 8a).…”
Section: Predicted Impact Of Transmitter and Exposure Contact Maskingmentioning
confidence: 99%
“…Study authors concluded that the experimental non-human primate species tested are permissive to SARS-CoV-2 infection, shed virus for pronged periods of time and display COVID-19-like disease, thereby providing suitable animal models for COVID-19 studies (Munster et al, 2020;Totura et al, 2020).…”
Section: Non-human Primatesmentioning
confidence: 99%